Animal Kingdom of Heaven Anthropozoological Aspects in the Late Antique World - Schaaf, Ingo (Millennium-Studien / Millennium Studies, 2019)
The essays collected in this volume apply an interdisciplinary approach to explore aspects of the relationship between animal and human in late antiquity. With a focus on ways that anthropozoological connections were defined in the emergent Christian religious discourse of the epoch, the authors contribute to our understanding of a thematic area largely neglected in previous research.